2000
DOI: 10.1152/jn.2000.84.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Startle Response During Human Gait

Abstract: While many studies have shown that there is a phase-dependent modulation of proprioceptive and exteroceptive reflexes during gait, little is known about such modulation for auditory reflexes. To examine how startle reactions are incorporated in an ongoing gait pattern, unexpected auditory stimuli were presented to eight healthy subjects in six phases of the step cycle during walking on a treadmill at 4 km/h. For both legs, electromyographic activity (EMG) was recorded in the biceps femoris (BF), the rectus fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
3
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 23 publications
2
23
3
1
Order By: Relevance
“…In contrast, TMS resulted in an average shortening of the long-latency onset of 16±30 ms in Experiment 1, with a maximum of 39.6 ms. The increased variability in long-latency onset for Experiments 1 and 2 is consistent with an auditory startle (Nieuwenhuijzen et al, 2000). The reduced variability in Experiment 3 further suggests that the auditory click was not triggering the subjects’ reactions in this final experiment.…”
Section: Resultssupporting
confidence: 62%
“…In contrast, TMS resulted in an average shortening of the long-latency onset of 16±30 ms in Experiment 1, with a maximum of 39.6 ms. The increased variability in long-latency onset for Experiments 1 and 2 is consistent with an auditory startle (Nieuwenhuijzen et al, 2000). The reduced variability in Experiment 3 further suggests that the auditory click was not triggering the subjects’ reactions in this final experiment.…”
Section: Resultssupporting
confidence: 62%
“…In contrast, startle does not have direct access to these spinal centres and this may explain why the basic gait-pattern is little affected. Nieuwenhuijzen et al [26] reported that startle was well integrated during gait, with only discrete kinematic changes that did not modify its course. In the same line, the results of Schepens and Delwaide [18] indicated that the step cycle was not modified when an unexpected loud sound was applied.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this unexpected, albeit consistent, alteration in the relative timing of lumbar flexor and extensor motor bursts in response to cervical afferent pathway activation was that it resulted from the unilateral mode of DR stimulation. Because peripheral sensory inputs from the left and right limb pairs are activated in phase opposition during actual stepping (Nieuwenhuijzen et al, 2000;Pearson, 2000), an additional series of experiments was conducted in which low-threshold DR afferents to both sides of the lumbar or cervical cord were stimulated alternately to more accurately reproduce the bilateral patterning of proprioceptive information input that occurs in vivo. However, in close correspondence with the effects of solitary DR activation (Fig, 5 B, C), a strictly antiphase relationship or an overall tendency toward coincident bursting continued to be expressed by homolateral flexor L2 and extensor L5 ventral roots in activity patterns elicited by alternating electrical stimulation of left and right L2 ( Fig.…”
Section: Influence Of Limb Sensory Inputs On Motor Burst-phase Relatimentioning
confidence: 99%